Adipokines as potential biomarkers for type 2 diabetes mellitus in cats - Sierawska, Olga; Niedźwiedzka-Rystwej, Paulina (Frontiers in Immunology, 2022)
Type 2 diabetes mellitus (T2DM) is no longer only a disease of humans, but also of domestic animals, and it particularly affects cats. It is increasingly thought that because of its unique characteristics, T2DM may belong not only to the group of metabolic diseases but also to the group of autoimmune diseases. This is due to the involvement of the immune system in the inflammation that occurs with T2DM. Various pro- and anti-inflammatory substances are secreted, especially cytokines in patients with T2DM. Cytokines secreted by adipose tissue are called adipokines, and leptin, adiponectin, resistin, omentin, TNF-α, and IL-6 have been implicated in T2DM. In cats, approximately 90% of diabetic cases are T2DM. Risk factors include older age, male sex, Burmese breed, presence of obesity, and insulin resistance. Diagnosis of a cat requires repeated testing and is complicated compared to human diagnosis. Adipokines seem to be an interesting proposition as biomarkers for the detection of T2DM, especially since they have an important function in obesity in cats. However, features shared by humans and cats in the pathogenesis of T2DM indicate that the cat could be a good model organism for this disease.